Thinned stone fruits are a source of polyphenols and antioxidant compounds. (21st June 2016) - Redondo, Diego; Arias, Esther; Oria, Rosa; Venturini, María E
Abstract: BACKGROUND: Thinned fruits are agricultural by‐products that contain large quantities of interesting compounds due to their early maturity stage. In this work, the phenolic profile and the antioxidant activity of six thinned stone fruits (apricot, cherry, flat peach, peach, plum and nectarine) have been investigated, focussing on proanthocyanidins. RESULTS: Thinned nectarine had the highest content of total phenols [67.43 mg gallic acid equivalents (GAE) g −1 dry weight (DW)] and total flavonoids (56.97 mg CE g −1 DW) as well as the highest antioxidant activity measured by DPPH scavenging (133.30 mg [Trolox equivalents (TE) g −1 DW] and FRAP assay (30.42 mg TE g −1 DW). Proanthocyanidins were very abundant in these by‐products, and the main phenolic group quantified in cherry (10.54 mg g −1 DW), flat peach (33.47 mg g −1 DW) and nectarine (59.89 mg g −1 DW), while hydroxycinnamic acids predominate in apricot, peach and plum (6.67, 22.04 and 23.75 mg g −1 DW, respectively). The low, mean degree of polymerisation of proanthocyanidins suggests that their bioavailability could be very high. CONCLUSIONS: This study shows that thinned stone fruit extracts might be used as antioxidants in foods or as a source of compounds with health‐related benefits that can be used in the pharmaceutical, cosmetic and food industries. © 2016 Society of Chemical Industry